2003
DOI: 10.1038/sj.ijo.0802377
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and inactivity in Chinese school-aged youth: the China Health and Nutrition Survey

Abstract: OBJECTIVE: To describe physical activity (PA) and inactivity levels and patterns in Chinese school children (aged 6-18 y). DESIGN: PA and inactivity were assessed in a youth cohort enrolled in the China Health and Nutrition Survey (CHNS) in 1997. SUBJECTS: A total of 1423 males (11.573.2 y) and 1252 females (11.573.3 y). MEASUREMENTS: PA and inactivity were assessed by self-reported usual activity (questionnaire). Children under 10 y were assisted by parents. RESULTS: Approximately 84% of Chinese youth activel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
131
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(145 citation statements)
references
References 30 publications
13
131
1
Order By: Relevance
“…Among Asian Bangladeshi, Chinese and Yemeni parents, time available for PA in childhood was decreased by pressure on children to achieve academically and participate in faith and language classes associated to their ethnic heritage. Emphasis on educational attainment in childhood as a barrier to PA is a recurrent theme in research with particular ethnic minority groups (e.g., Chinese [48], Middle Eastern [11], Bangladeshi, Pakistani and Black African [17] populations) living in Western countries. Given parental concern about education, relating the benefits of PA to improved concentration and cognitive functioning [49,50] may increase engagement in activities.…”
Section: Discussionmentioning
confidence: 99%
“…Among Asian Bangladeshi, Chinese and Yemeni parents, time available for PA in childhood was decreased by pressure on children to achieve academically and participate in faith and language classes associated to their ethnic heritage. Emphasis on educational attainment in childhood as a barrier to PA is a recurrent theme in research with particular ethnic minority groups (e.g., Chinese [48], Middle Eastern [11], Bangladeshi, Pakistani and Black African [17] populations) living in Western countries. Given parental concern about education, relating the benefits of PA to improved concentration and cognitive functioning [49,50] may increase engagement in activities.…”
Section: Discussionmentioning
confidence: 99%
“…China is a newly industrializing country that is currently experiencing a severe challenge in the area of health and nutrition [18,19]. Studies have shown that nutritional deficiencies and over-nutrition are significant in many parts of China and that the problem is growing [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…5,7 Similar to many other countries, 8 China suffers the burden of declining PA levels and increasing sedentary behavior among school-aged children, the likely result of broad social changes. [9][10][11] Shanghai, located on the east coast of China, is one of the biggest and most populous cities in both China and the world, with a population of more than 24 million. The proportion of children and youth from Shanghai (the most developed city in China) who meet the recommendation of 1 hour of MVPA everyday is very low.…”
mentioning
confidence: 99%